2021
DOI: 10.3390/life11101091
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Tensegrity in Microgravity

Abstract: In order for Man to venture further into Space he will have to adapt to its conditions, including microgravity. Life as we know it has evolved on Earth with a substantial gravitational field. If they spend considerable time away from Earth, astronauts experience physiological, mental, and anatomical changes. It is not clear if these are pathological or adaptations. However, it is true that they experience difficulties on their return to stronger gravity. The cytoskeleton is a key site for the detection of grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…According to the latest Global Cancer Observatory survey from 2020, thyroid carcinomas (TC) are responsible for 586,000 cancer cases worldwide [72]. The American Cancer Society recently estimated that there will be about 43,800 new cases of TC (11,860 in men and 31,940 in women) and about 2230 deaths from this type of tumor (1070 men and 1160 women) in the United States in 2022 [73].…”
Section: Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…According to the latest Global Cancer Observatory survey from 2020, thyroid carcinomas (TC) are responsible for 586,000 cancer cases worldwide [72]. The American Cancer Society recently estimated that there will be about 43,800 new cases of TC (11,860 in men and 31,940 in women) and about 2230 deaths from this type of tumor (1070 men and 1160 women) in the United States in 2022 [73].…”
Section: Thyroid Cancermentioning
confidence: 99%
“…For example, the virulences of Listeria monocytogenes , methicillin-resistant Staphylococcus aureus , Enterococcus faecalis , and Candida albicans were shown to decrease in microgravity [ 9 ]. In mammalian cells, µ g is able to disrupt the cytoskeleton [ 10 ], which is thought to be a major factor for cellular graviperception [ 11 ]. It was also found that cell growth under µ g could induce a spontaneous assembly of three-dimensional (3D)-tissue constructs from cell monolayers, ranging from more amorphous multicellular spheroids (MCS) to more complex vascular intima-like structures [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viewing the body in terms of tensegrity, i.e., a relationship based on the principle that structures remain in a close relationship that impacts on each structure (an increase in tension in one element brings about an increase in tension of the others) [22,73,74]. The human body functions as a whole to counteract the force of gravity.…”
Section: Discussionmentioning
confidence: 99%